Healthy Living: Reliable Web Sites - Linda B. Bobroff; Leigh Ann Martin (EDIS, 2009)
Revised! FCS-8587-Eng, a 2-page fact sheet by Linda B. Bobroff and Leigh Ann Martin, lists trustworthy sites related to nutrition, health, food safety, and resources for older people. Published by the UF Department of Family Youth and Community Sciences, July 2009.